Paradoks Kemakmuran: Mengungkap Dampak Produksi Kelapa Sawit terhadap Kemiskinan di Pedesaan Indonesia - Ikhsan, Ikhsan; Hajad, Vellayati; Maulida, irham (Indonesian Journal Publisher, 2025)
This study analyzed the prosperity paradox arising from palm oil production in Indonesia, with a focus on its impact on rural poverty. Despite the industry’s significant contribution to economic growth, many smallholder farmers and local communities remain trapped in poverty. Using a Systematic Literature Review (SLR) method, the study comprehensively identifies and synthesizes relevant evidence on this issue. The findings show that while the palm oil sector creates jobs and increases incomes for some, inequities in the distribution of benefits, limited access to resources, and adverse environmental impacts are significant barriers to smallholder well-being. The conclusion from this study shows that there is a need for greater attention from the Indonesian government to improve smallholder well-being and ensure environmental sustainability in the palm oil industry through inclusive policies. Recommendations include increased support to develop farmer capacity and protection of local community rights. With these steps, it is hoped that the benefits of the palm oil industry can be felt more equitably by all parties involved.